Geographically Discriminatory Trade Arrangements - Hamilton, Bob; Whalley, John (The Review of Economics and Statistics, 1985)
A bstract-An eight-region numerical general equilibrium model of global trade is used to investigate the impacts of various geographically discriminatory trade policy arrangements (GDAs) on regional trade and welfare. Results suggest that the important factors determining gains and losses in any GDA are such issues as whether initial levels of protection are asymmetric, the relative sizes of participating regions, and the pattern of trade between participating and non-participating countries. Results also appear to confirm the implication of Wonnacott and Wonnacott (1981) that the gain from reducing a partner's tariff is typically a more important consideration in evaluating potential benefits from a customs union, than the traditional concerns of trade creation and trade diversion.